Islamic moral judgement on abortion and its nursing applications: expository analysis - Mohamad Firdaus, Mohamad Ismail; Hashi, Abdurezak Abdulahi; Nurumal, Mohd. Said; Md Isa, Muhammad Lokman (Elsevier, 2018)
Health workers, like nurses are tasked to save the lives of their patients, however, there are instances in which health workers have to deal with difficult cases in taking a life, such as abortion. Scholars in the field of healthcare assert that abortion is morally justified if it is sought for health reasons. Nevertheless, there are a number of cases in which abortion is sought on other grounds other than health, such as the individual choice to do so. Can a nurse refuse to provide their professional service towards these people? This paper uses analytical and comparative methods to address ethical issues in abortion from the Islamic and conventional perspectives.